Latin American structuralism and neomarxists: the origin of underdevelopment process of the periphery (2013)
This paper seeks to establish a comparative analysis between structuralist and neo-marxists, to thereby recover the old debate about what is development. For this purpose, through a literature review that will depart from the influences of the classics and Marx in development economics. As well, it will recove the contributions of several prominent figures from each school in order to trace the theoretical connections between the two approaches to development economics. In addition, itwill analyse the concept of development, the origin of the underdevelopment of the periphery, the barriers to development and development strategies advocated by structuralists and neo-marxists.